Differences of nitrogen metabolism in date palm (Phoenix dactylifera) seedlings subjected to water deprivation and salt exposure. (29th December 2022) - Du, Baoguo; Winkler, Jana Barbro; Ache, Peter; White, Philip J; Dannenmann, Michael; Alfarraj, Saleh; Albasher, Gadah; Schnitzler, Joerg-Peter; Hedrich, Rainer; Rennenberg, Heinz
Abstract: Drought and salt exposure are among the most prevalent and severe abiotic stressors causing serious agricultural yield losses, alone and in combination. Little is known about differences and similarities in the effects of these two stress factors on plant metabolic regulation, particularly on nitrogen metabolism. Here, we studied the effects of water deprivation and salt exposure on water relations and nitrogen metabolites in leaves and roots of date palm seedlings. Both, water deprivation and salt exposure had no significant effects on plant water content or stable carbon (C) and nitrogen (N) isotope signatures. Significant effects of water deprivation on total C and N concentrations were only observed in roots, i.e., decreased total C and increased total N concentrations. Whereas salt exposure initially decreased total C and increased total N concentrations significantly in roots, foliar total C concentration was increased upon prolonged exposure. Initially C/N ratios declined in roots of plants from both treatments and upon prolonged salt exposure also in the leaves. Neither treatment affected soluble protein and structural N concentrations in leaves or roots, but resulted in the accumulation of most amino acids, except for glutamate and tryptophan, which remained stable, and serine, which decreased, in roots. Accumulation of the most abundant amino acids, lysine and proline, was observed in roots under both treatments, but in leaves only upon salt exposure. This finding indicates a similar role of these amino acids as compatible solutes in the roots in response to salt und drought, but not in the leaves. Upon prolonged treatment, amino acid concentrations returned to levels found in unstressed plants in leaves of water deprived, but not salt exposed, plants. The present results show both water deprivation and salt exposure strongly impact N metabolism of date palm seedlings, but in a different manner in leaves and roots.